2006
DOI: 10.1080/17441690600668106
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV/AIDS/STI knowledge, attitudes, and behaviours among the youth in Port Loko, Sierra Leone

Abstract: Sierra Leone suffered from 11 years of civil war (1991-2002) resulting in tens of thousands of deaths and mutilations and massive population displacement. In 2001, ARC International, Sierra Leone, conducted a baseline survey of 244 female youth and 293 male youth on knowledge, attitudes, and behaviours around HIV/AIDS and STIs in Port Loko. In 2003, following 2 years of HIV prevention activities, a comparable post-intervention survey of 250 female and 299 male youth was performed. Comparison of baseline and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 4 publications
2
29
0
Order By: Relevance
“…They were conducted in nine African countries which included Uganda, Ethiopia, DR Congo, Somalia, Kenya, Nigeria, Djibouti, Rwanda and Sierra Leone [6,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. These consisted of eight applied qualitative, five quantitative and two mixed-method study designs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They were conducted in nine African countries which included Uganda, Ethiopia, DR Congo, Somalia, Kenya, Nigeria, Djibouti, Rwanda and Sierra Leone [6,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. These consisted of eight applied qualitative, five quantitative and two mixed-method study designs.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were performed exclusively with young girls and women of age groups 10–24, 12 other studies included them as one of the groups in total population, e.g., among women of reproductive age or adolescents including boys and girls. One study [16] reported the results before and after the intervention. For the purpose of this review we have used the baseline data from the above mentioned study on HIV/STDs knowledge and attitudes among young displaced girls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations